2017
DOI: 10.7196/sajog.1274
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of subacute uterine inversion by Haultain’s method: A case report

Abstract: CASE REPORTUterine inversion is a rare but potentially life-threatening obstetric emergency of unknown aetiology, which is often associated with inadvertent traction on the umbilical cord before separation of the placenta. Here we report a case of a 26-year-old woman who presented with a day's history of uterine inversion after an attempt to remove a retained placenta following a second-trimester miscarriage. Reduction was attempted in casualty without success and she was taken to theatre for surgical reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The other factors (maternal, placental, fetal, and iatrogenic) are more likely at advanced gestations. Ziki et al had reported that attempts to deliver the placenta by cord traction might cause an inversion at this early gestation, but our client denied this action 10 …”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The other factors (maternal, placental, fetal, and iatrogenic) are more likely at advanced gestations. Ziki et al had reported that attempts to deliver the placenta by cord traction might cause an inversion at this early gestation, but our client denied this action 10 …”
Section: Discussionmentioning
confidence: 71%
“…The reported incidence of puerperal uterine inversions varies widely but is higher in remote rural areas where access to emergency obstetric care is inadequate. 8,10,11 Post-abortal uterine inversions are infrequent events, with only a handful of cases reported so far in our literature search, all from low-middle income nations. 6,7 The exact cause of puerperal uterine inversions remains undefined, with about 50% of cases reported in low-risk women with no precipitating factor identified.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations